감염성 각막염 의심환자에서 분리한 Fluoroquinolone 항생제 내성균주의 동정 및 gyrA 유전자 분석 - 나훈택; 정맹식; 김홍선; 김수영 (대한시과학회지, 17(2), 2015)
목적: 콘택트렌즈의 부작용으로 감염성 각막염이 의심되는 환자에서 분리한 균주들을 동정하고, fluoroquinolone 항생제 내성균주를 감별하여 내성기전에 관여하는 gyrA 유전자를 분석해 내성의 원인을 알아보고자 한다. 방법: 감염성 각막염이 의심되는 기질성 침입 환자 30명을 대상으로, 각막에서 분리한 균주를 Ofloxacin(5㎍/㎖), Ciprofloxacin(5㎍/㎖), Levofloxacin(5㎍/㎖) 항생제 배지에 배양하여 16S rRNA gene PCR 방법으로 동정하였다. 디스크 확산법으로 내성균주를 감별하고, genomic DNA를 추출하여 PCR를 통해 증폭한 후 gyrA QRDR 부위의 유전자를 분석하였다. 결과: Ofloxacin이 첨가된 배지에서 배양된 균주는 Achromobacter xylosoxidans(N101, N102), Staphylococcus epidermidis(N105)로 동정되었고, Ciprofloxacin이 첨가된 배지에서 배양된 균주는 Achromobacter xylosoxidans(N101, N102), Staphylococcus epidermidis(N103, N104, N105, N106), Staphylococcus warneri(N107), Staphylococcus hominis(N108), Staphylococcus saprophyticus(N109), Alcaligenes sp.(N110)로 동정되었다. 항생제 디스크 확산법으로 Staphylococcus epidermidis(N105)는 Ofloxacin에 내성, Ciprofloxacin과 Levofloxacin은 중간내성으로 나타났으며, gyrA 유전자의 분석 결과 QRDR부위에서 Ser(TCT)84→Phe(TTT)으로 아미노산 변이가 관찰되었다. 결론: 감염성각막염 의심환자 각막에서 그람양성균 7균주, 그람음성균 3균주가 동정되었다. fluoroquinolone 항생제 감수성 검사에서 내성균주가 나타났으며, gyrA 유전자의 codon 84 부위에서 아미노산 변이가 나타나 내성에 영향을 미치고 있다는 것을 확인할 수 있었다. 향후 항생제의 지속적인 사용으로 많은 내성균주들이 나타날 것이라 예측되며 fluoroquinolone 항생제를 사용할 때 내성에 대한 주의가 필요할 것으로 생각된다. Purpose: As a side effect contact lenses identified the isolates from patients who are suspected to be infectious keratitis, by differentiating a fluoroquinolone antibiotic resistant strains analyzed the gyrA genes involved in resistance mechanisms to investigate the cause of the resistance. Methods: Targeting the stromal invasion 30 patients suspected infectious keratitis, isolates from the cornea were cultured in Ofloxacin(5㎍/㎖), Ciprofloxacin(5㎍/㎖), Levofloxacin(5㎍/㎖) antibiotic medium was identified by 16S rRNA gene PCR method. Differentiating the resistant strains by the disk diffusion method, and to extract genomic DNA and then amplified through the PCR, analyzed genes gyrA QRDR region. Results: Strains cultured on the medium supplemented with Ofloxacin were identified as Achromobacter xylosoxidans(N101, N102), Staphylococcus epidermidis(N105), and strains cultured in the medium supplemented with Ciprofloxacin were identified as Achromobacter xylosoxidans(N101, N102), Staphylococcus epidermidis(N103, N104, N105, N106), Staphylococcus warneri(N107), Staphlococcus hominis(N108), Staphylococcus saprophyticus(N109), and Alcaligenes sp.(N110). Staphylococcus epidermidis(N105) was resistant to Ofloxacin, Ciprofloxacin and Levofloxacin was shown to intermediate resistant, the amino acid mutation observed by Ser(TCT)84→Phe (TTT) the analysis results QRDR region of gyrA gene. conclusions: In corneal of infectious keratitis suspected patients, seven strains of gram-positive and three strains of gram-negative were identified. observed resistant strain in the antimicrobial susceptibility test, in codon 84 region of the gyrA gene was confirmed that affects the resistance appeared that amino acid mutations. the future, predicted would occur many resistant strains to continued use of antibiotic, will be needed attention to resistance when using a fluoroquinolone antibiotic. KCI Citation Count: 1